PHYSICO-CHEMICAL INVESTIGATIONS OF THE COMPOSITION OF BASALT OF THE AYDARKUL DEPOSIT - Razzokov Khasan; Nazarov Sayfulla; Rashidova Ra’no; Rasulov Mirzo (Journals Park Publishing, 2023)
The chemical composition of the basalts of the Aydarkul deposit is studied in the article. To determine the changes in inorganic substances in basalts, the IR spectrometry method was used, which made it possible to determine the state of the structural features of the basalt rock and constituent materials. It has been established that the polyoxide composition of basalt rocks is due to the bonding forces between oxygen and the chemical elements of metals, which form a rigid crystal lattice. The bonds between oxygen and elements such as Al, Fe, Mg, K, N, Ti and Si stand out in particular.
Keywords: Mud, basalt, crystal lattice, dipole moment, mineral, rock.